The Role of Competencies in Encouraging Organizational Commitment through Organizational Culture - Zamroni; Erwansyah (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the effect of Competence and Motivation on Organizational Commitment with Organizational Culture as an intervening variable at the Representative Office of Bank Indonesia in Medan, North Sumatra, and Aceh. This research employs a quantitative approach using the Structural Equation Modeling (SEM) method based on SmartPLS 3.0. The research sample consists of employees working at the Representative Office of Bank Indonesia in Medan and Aceh, selected using purposive sampling techniques. Data were collected through questionn    aires distributed using a Likert scale ranging from 1 to 5.          The results indicate that Competence and Motivation have a positive and significant effect on Organizational Culture, and Organizational Culture has a significant effect on Organizational Commitment. Competence also has a direct and significant effect on Organizational Commitment, while Motivation does not have a direct effect on Organizational Commitment. However, Organizational Culture is proven to significantly mediate the relationship between Competence and Motivation on Organizational Commitment. Therefore, Organizational Culture plays an essential role in strengthening the influence of Competence and Motivation on enhancing employees’ Organizational Commitment.